MR enhancement of brain lesions: increased contrast dose compared with magnetization transfer. - Knauth, Michael; Forsting, Michael; Hartmann, Marius; Heiland, Sabine; Balzer, Th.; Sartor, Klaus (American journal of neuroradiology, 1996)
PURPOSE To compare image contrast and lesion conspicuity of enhancing intracranial lesions obtained with T1-weighted and magnetization transfer T1-weighted spin-echo sequences after administration of standard (0.1 mmol/kg body weight) and triple doses of gadobutrol. - METHODS Twenty-four patients with a total of 34 enhancing intracranial lesions were studied with T1-weighted and magnetization transfer T1-weighted spin-echo MR imaging. An incremental dose technique was used with intravenous injections of 0.1 and 0.2 mmol/kg body weight gadobutrol. Lesion-to-white matter contrast and white matter-to-edema contrast were calculated. - RESULTS The lesion-to-white matter contrast of the magnetization transfer T1-weighted studies was significantly higher than that of the T1-weighted studies when identical doses of gadobutrol were compared. The lesion-to-white matter contrast was not significantly different on the triple-dose T1-weighted study and the standard-dose magnetization transfer T1-weighted study. Two lesions were visible only on the standard-dose magnetization transfer T1-weighted and the triple-dose studies. - CONCLUSION Standard-dose magnetization transfer T1-weighted and triple-dose T1-weighted spin-echo MR studies are equally well suited to increase the lesion-to-white matter contrast in patients with enhancing intracranial lesions. Triple-dose magnetization transfer T1-weighted studies further increase lesion-to-white matter contrast but do not show additional lesions.
Gesehen am 19.02.2025